Bats - Faisal Ali, Bin Anwarali Khan; Norfarhana, Mazlan; Julius Willian, Dee; Muhd Amsyari, Bin Morni; Qhairil Shyamri, Rosli; Shafri, Semawi; Mohd Ridwan, Abd Rahman; Roberta Chaya Tawie, anak Tingga; Mohd-Azlan, Jayasilan (Natural History Publications (Borneo) Sdn. Bhd., Kota Kinabalu, UNIMAS Publisher, Sarawak Forestry Corporation Sdn Bhd, Kota Samarahan, 2018)
The forests of Santubong National Park include mangroves, mixeddipterocarp, heath (Kerangas), and hill forests. This complex environment supports a rich bat diversity, as also observed at the nearby Bako National Park and Tanjung Datu National Park. Observing this diversity is sometimes not an easy affair, as the upland areas are challenging for the deployment of traps. The biodiversity enumerated in this chapter is based on trapping effort that focused on the lower parts of the Park, along established trails. Bat trapping was conducted during two separate feld expeditions, in the months of November 2015 and October 2016, with eight and six trapping nights duration, respectively. Harp traps and mist-nets were set along trails and small creeks.